A review on the challenges in machining of ceramics. (2021) - Bharathi, V.; Anilchandra, A.R.; Sangam, Shantanu Sanjay; Shreyas, S.; Shankar, Siddesh B.
Abstract: Ceramics are solid compounds largely consisting of inorganic and non-metallic components bound by strong ionic and/or covalent bonds. Advanced ceramics such as Zirconia, Silicon carbide, Alumina and Silicon Nitride, find extensive applications in the field of aerospace, military and defence industry due to their enhanced mechanical and physical properties such as excellent refractoriness, high compressive strength, chemical inertness and hardness. While such properties are highly desirable in extreme environments, the inherent high brittleness and low shear strength poses a significant challenge to their machinability. Machining of ceramics is also plagued by surface damage, excessive tool wear, and edge chipping when machined using conventional techniques; non-conventional techniques such as Electric Discharge Machining (EDM) and Abrasive Water Jet machining are characterized by poor surface finish and excessive occurrence of pits, respectively. Achieving dimensional accuracy and minimizing collateral damage such as surface cracks are the key challenges in the machining of ceramics. In this review work, the machining parameters significantly influencing the machining of ceramics using non-conventional processes such as, Ultrasonic machining and Laser machining have been discussed. In contact type of non-conventional machining, feed rate significantly affects the surface finish while in the non-contact type laser scan speed seems to be deciding input parameter in machining ceramics. Rotary Ultrasonic Machining and Laser Assisted Machining (LAM) seem to be the most popular techniques for machining of ceramics, mainly due to better metal removal rate and almost defect-free surface compared to the conventional machining processes.